FINANCIAL TECHNOLOGY INNOVATION: ANALYSIS OF PEER-TO-PEER (P2P) LENDING IN INDONESIA - Ahmad Sabbi; Bayu Fajar Susanto (Indragiri Research Center (ingreat), 2024)
This study aims to analyze Peer-to-Peer (P2P) Lending as an innovation in financial technology in Indonesia. P2P Lending connects lenders and borrowers directly through digital platforms, thereby providing broader access for individuals and Micro, Small, and Medium Enterprises (MSMEs) that often struggle to obtain financing from traditional financial institutions. In this context, the study employs a descriptive quantitative approach using content analysis, gathering data from various relevant online sources, including official reports and academic articles. The findings indicate that P2P Lending offers several benefits, such as competitive interest rates, faster application processes, and diversified investment options for lenders. However, the industry also faces several challenges, including high credit risk and an underdeveloped regulatory framework. Credit risk is a primary concern, as the possibility of borrowers defaulting on loans can lead to significant losses for lenders. Additionally, existing regulations need to be strengthened to protect all parties involved and to ensure transparent practices. The conclusions of the study emphasize the importance of a comprehensive understanding of P2P Lending, including its working mechanisms and the challenges it faces, to maximize its benefits and mitigate existing risks. These findings are expected to serve as a reference for P2P Lending platform developers, regulators, and other stakeholders in creating a more inclusive and sustainable financial ecosystem in Indonesia.